A comprehensive review of SHP2 and its role in cancer - Asmamaw, Moges Dessale; Shi, Xiao-Jing; Zhang, Li-Rong; Liu, Hong-Min (Cellular oncology (Dordrecht), 2022)
Src homology 2-containing protein tyrosine phosphatase 2 (SHP2) is a non-receptor protein tyrosine phosphatase ubiquitously expressed mainly in the cytoplasm of several tissues. SHP2 modulates diverse cell signaling events that control metabolism, cell growth, differentiation, cell migration, transcription and oncogenic transformation. It interacts with diverse molecules in the cell, and regulates key signaling events including RAS/ERK, PI3K/AKT, JAK/STAT and PD-1 pathways downstream of several receptor tyrosine kinases (RTKs) upon stimulation by growth factors and cytokines. SHP2 acts as both a phosphatase and a scaffold, and plays prominently oncogenic functions but can be tumor suppressor in a context-dependent manner. It typically acts as a positive regulator of RTKs signaling with some inhibitory functions reported as well. SHP2 expression and activity is regulated by such factors as allosteric autoinhibition, microRNAs, ubiquitination and SUMOylation. Dysregulation of SHP2 expression or activity causes many developmental diseases, and hematological and solid tumors. Moreover, upregulated SHP2 expression or activity also decreases sensitivity of cancer cells to anticancer drugs. SHP2 is now considered as a compelling anticancer drug target and several classes of SHP2 inhibitors with different mode of action are developed with some already in clinical trial phases. Moreover, novel SHP2 substrates and functions are rapidly growing both in cell and cancer. In view of this, we comprehensively and thoroughly reviewed literatures about SHP2 regulatory mechanisms, substrates and binding partners, biological functions, roles in human cancers, and different classes of small molecule inhibitors target this oncoprotein in cancer.